BACKWARD LEARNING MODEL USING MEDIA TOOLS - Usra, Meirizal (Sriwijaya University Learning and Education International Conference, 2018)
The aim this research is to develop a model salto backward exercise using media tool and to obtain empirical data about the effectiveness of salto backward exercise model using media tool. This a research and development, research consisting of ten steps. These steps are (1) Needs and observation analysis, (2) Information gathering, (3) Preparation of the initial product, (4) Expert evaluation, (5) Revision, (6) Small group test using 10 subjects, (7) Revision ,, (8) Large group trial using 20 subjects, (9) Revision of final product, (10) Dissemination. From the research and procedures performed above, the product is a model of back salto exercise using a media tool that consists of 13 forms of models. The back-to-back salto exercise model using this developed media tool comes from advice or expert input and evaluation, including 2 backward and 1 from sports education. The results obtained the model of backward salto exercise using this tool media is good and can be used athletes. Suggestion this research that this product can be as one way to improve ability and achievement of athlete, and specially trainer that this product can be reference to train athletes.